Marketing strategies for tourism development in frontier and outermost Talaud Islands - Agus Supandi Soegoto; Daniel Peterson Silaban; Deasy Soeikromo; Andini P. Soegoto (Jurnal Ekonomi Indonesia, 2026)
This study examines the role of marketing strategies in developing frontier and outermost island tourism destinations, with a focus on the Talaud Islands, North Sulawesi, Indonesia. Despite their rich natural and cultural potential—ranging from pristine coastal landscapes and marine biodiversity to distinctive culinary and cultural heritage-the Talaud Islands remain underdeveloped due to weak promotion, limited accessibility, and infrastructural constraints. A qualitative descriptive method was applied, combining interviews with 35 domestic and international tourists and secondary data from official sources. Strategic analysis was conducted using SWOT, supported by the Internal Factor Analysis Summary and External Factor Analysis Summary. The IFAS results revealed strong natural assets but limited optimization, while EFAS highlighted opportunities in ecotourism demand and digital promotion, countered by competition from more accessible destinations and weak connectivity. The SWOT analysis generated four sets of strategies, focusing on digital branding, eco-cultural events, infrastructure development, and community engagement. The findings underscore the importance of adaptive, collaborative, and sustainable marketing approaches to enhance Talaud’s visibility and competitiveness. This study offers policy and managerial insights to strengthen the positioning of frontier islands as distinctive destinations in Indonesia’s national and global tourism landscape.